2015
DOI: 10.1111/php.12523
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just Light: Clinical Relevance of Light Perception in the Nosocomial Pathogen Acinetobacter baumannii and Other Members of the Genus Acinetobacter

Abstract: A summary of the major findings concerning light modulation in Acinetobacter baumannii, which governs aspects related to the success of this microorganism as a nosocomial pathogen, is presented. Particularly, the evidence shows that light modulates the ability of the bacteria to persist in the environment, its virulence against eukaryotic hosts and even susceptibility to certain antibiotics. The light signal is sensed through different mechanisms, in some cases involving specialized photoreceptors of the BLUF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…These bacterial responses depended on the expression of the Ab ATCC 17978 A1S_2225 gene named blue-light-sensing A ( blsA ). The light modulated motility and biofilm formation (Ramírez et al, 2015a), more precisely motility and formation of biofilms and pellicles, were observed only when bacterial cells were incubated in darkness. Furthermore, the same authors demonstrated that susceptibility to minocycline and tigecycline, two antibiotics used for the treatment of MDR A. baumannii infections, was modulated by light (Ramírez et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial responses depended on the expression of the Ab ATCC 17978 A1S_2225 gene named blue-light-sensing A ( blsA ). The light modulated motility and biofilm formation (Ramírez et al, 2015a), more precisely motility and formation of biofilms and pellicles, were observed only when bacterial cells were incubated in darkness. Furthermore, the same authors demonstrated that susceptibility to minocycline and tigecycline, two antibiotics used for the treatment of MDR A. baumannii infections, was modulated by light (Ramírez et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Retrotranscription and qRT-PCR analysis were done as described in reference 39 , using primers listed in Table S2 in the supplemental information. Data are presented as NRQ (Normalized relative quantities) calculated by the qBASE method 40 , using recA and rpoB genes as normalizers 6 .…”
Section: Methodsmentioning
confidence: 99%
“…7A). The participation of BOF proteins in biofilm formation, motility, and virulence in response to quorum-sensing and hormonal signals (10) has been reported in some organisms. Moreover, a cluster of genes coding for a de-Nacetylase of the phosphatidylinositol-glycan biosynthesis class L protein (PIG-L) superfamily (DJ41_1943), followed by a methyltransferase gene (DJ41_1944) and a glycosyltransferase gene (DJ41_1955, which changes only 0.5-fold with respect to dark conditions), also located in the vicinity of blsA, are upregulated under blue light.…”
Section: Novel Traits Modulated By Light In a Baumanniimentioning
confidence: 99%
“…Finally, we have presented evidence indicating that light modulates susceptibility to minocycline and tigecycline antibiotics in Acinetobacter, as well as other clinically relevant pathogens, by a BlsA-independent mechanism that most likely involves induction of the expression of resistance genes by singlet oxygen (8,10).…”
mentioning
confidence: 99%